Existence and uniqueness solutions for nonlinear fractional differential equations with fractional integral boundary conditions. Issue 7 (3rd October 2021) - Abdul-Razaq, N. A.; Mohammed, H. S.; Housen, N. L.
Abstract: The theory of Schuder fixed point and Banach contraction theorems are used to explain the behavior of solution for differential equation of fractional order β ∈ (2, 3] with fractional integral limit conditions given by .We prove the existence and uniqueness solution of the above equations.